The Influence of Institutional and Regulatory Aspects and Information on Waste Management on Community Intention to Support Waste Management in the Kahayan River Basin, Central Kalimantan - Sitinjak, Tarita Aprilani; Trissan, Whendy; Perkasa, Petrisly; Permanasuri, Ni Putu Diah Agustin; Kurniawati, Mega; Nathanael, Nathanael; Ruslan, Ruslan (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2025)
Disposing of domestic waste into the river remains a common practice among the majority of residents along the Kahayan River in Palangka Raya City impacting pollution, flooding, and public health. This study aims to analyze variables influencing people's intention to support domestic waste management activities. The study was conducted in Mendawai and Flamboyan Bawah, densely populated settlements on the banks of the Kahayan River in Palangka Raya City. One hundred respondents were selected with a non-probability technique and interviewed to obtain information on infrastructure (X1), economy (X2), location (X3), institutions and regulations (X4), and waste management information (X5) aspects. Descriptive statistics was utilized to understand respondent characteristics and Structural Equation Model-Partial Least Square (SEM-PLS) was applied to determine the effect of each variable. This study found that the majority of respondents were women (n = 44), housewives (n = 40), and over 35 years old (n = 46). The analysis results show that increasing the information aspect of waste management will increase the community's intention to support domestic waste management activities by 40.1% (P = 0.001). Meanwhile, increasing the institutional and regulatory aspects has an effect of 29.2% (P = 0.002). The other three variables did not show significant results (P > 0.05). The results of this study reveal that the community's intention to support domestic waste management activities is influenced by the informational, institutional and regulatory aspects. Establishing community-based institutions that able to provide ongoing support presents a viable strategy for promoting sustainable behavioral change.